Bridging Gaps in Madrasah Human Resource Management: Lessons from Sigi, Indonesia - Mastura Minabari; Muhammad Sarib Abdul Rasak; Samintang Samintang; Ruslin Ruslin; Wadinlada Thuratham; Masmur Mansur; Hijrah Syam (Institute of Multidisciplinary Research and Community Service, 2026)
Over the past two decades, the quality of human resources (HR) in Islamic educational institutions has become a strategic priority in Indonesian education policy. This is true, as madrasahs, being Islamic educational institutions, have a distinctive role in imparting religious values and fostering students' intellectual and professional development. Objective: This study analyzes the implementation of Human Resource Management (HRM) practices in madrasahs, focusing on recruitment, professional development, mentorship, and career advancement, as well as the alignment of these activities with managerial concepts and Islamic humanistic ideals. Methods: The study employed a mixed-methods research approach. Quantitative data were obtained via online questionnaires from 49 respondents. In contrast, qualitative data were gathered through interviews with 28 participants, including principals, deputy principals, teachers, and educational staff from five madrasahs in Sigi, Indonesia. The data analysis used descriptive statistics and Pearson correlation in SPSS 23 for quantitative data, and thematic analysis for qualitative data, incorporating triangulation to augment validity. Findings: Madrasahs are evolving towards more professional, competency-oriented approaches to human resource management. Nonetheless, considerable contradictions persist between formal administrative systems and humanistic principles, particularly with recruitment equity, fair career advancement, and the sustainability of professional development programs. These difficulties illustrate disparities in the comprehension and application of HRM principles across institutions. Conclusion: The research finds that successful HRM reform in madrasahs requires integrating Human Relations Theory and Organizational Behavior Theory to align Islamic ideals with modern managerial practices. The findings provide valuable insights for policymakers and educational leaders aiming to enhance HRM systems in madrasahs, while acknowledging limits due to potential bias in online interviews and restricted opportunity for comprehensive qualitative analysis. Keywords: human resource management, madrasah, recruitment, professional development, teacher career.